2011
DOI: 10.1111/j.1748-3743.2011.00282.x
|View full text |Cite
|
Sign up to set email alerts
|

Transferring from an acute hospital and settling into a subacute facility: the experience of patients with dementia

Abstract: Nurses who understand the specific needs of patients with dementia can develop ways of working with patients to ensure person-centred care. More conversations with people with dementia are needed to investigate how this can be achieved. Orientation procedures should ensure that support for people with dementia is optimized during the settling-in phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
73
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(75 citation statements)
references
References 46 publications
2
73
0
Order By: Relevance
“…The patronising attitude of the staff was not altogether lost on the patients, some of whom remarked on this (Cowdell , Digby et al . ). In the study by Edvardsson and Nordvall () one of the patients felt the stigmatisation acutely: ‘… they toss me my sandwiches the way you would do a dog’.…”
Section: Methodsmentioning
confidence: 97%
See 3 more Smart Citations
“…The patronising attitude of the staff was not altogether lost on the patients, some of whom remarked on this (Cowdell , Digby et al . ). In the study by Edvardsson and Nordvall () one of the patients felt the stigmatisation acutely: ‘… they toss me my sandwiches the way you would do a dog’.…”
Section: Methodsmentioning
confidence: 97%
“…, Digby et al . , Edvardsson et al . , Digby & Bloomer ) which limits the transferability of the results.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible that this variability in trunk position observed for the DG participants was the result of many factors, including general motor restlessness (Zuidema, Derksen, Verhey, & Koopmans, 2007), difficulty staying orientated to the purpose of the activity (Joray, Herrmann, Mulligan, & Schnider, 2004), or decreased ability to cope with the testing situation due to cognitive problems associated with dementia. The testing environment was new for participants and it has been found that people living with dementia can feel anxious when faced with a novel situation (Digby, Moss, & Bloomer, 2012). However, these proposed explanations are only speculative, as levels of motor restlessness, orientation, and anxiety during the task were not specifically assessed.…”
Section: Variablesmentioning
confidence: 99%